Hesperetin ameliorates lipopolysaccharide‐induced acute lung injury via the miR‐410/SOX18 axis. Issue 12 (6th August 2020) - Dong, Junying; Zhou, Haiyan; Zhao, Hongqin; Zhao, Yanhong; Chang, Can
Abstract: Hesperetin (Hesp), a dihydroflavone, has a wide range of pharmacological activities, including antioxidant, anti‐inflammatory, and antitumor effects, as well as cardiovascular protection. It also has protective effects against acute lung injury (ALI); however, the exact mechanism remains unclear. In the present study, the protective effects and mechanism of Hesp in the lungs were investigated. Hematoxylin and eosin staining was used to examine pathological changes in the lungs. Enzyme‐linked immunosorbent assay was used to detect proinflammatory cytokine levels. In addition, reverse transcription‐quantitative polymerase chain reaction and Western blot analysis were used to observe the transcription and translation changes in the related genes, respectively. The results indicate that Hesp not only improves histopathological changes in the lungs but decreases the wet/dry ratio. In addition, total cell counts and the number of neutrophils and macrophages were lower in the bronchoalveolar fluid after Hesp treatment, consistent with the change in proinflammatory cytokine levels. MicroRNA‐410 (miR‐410) levels were significantly lower in the lung tissues of ALI mice and were reversed after Hesp treatment. Furthermore, miR‐410 overexpression due to injection with agomiR‐410 produced similar protective effects as Hesp. However, blocking miR‐410 inhibited the protective effects of Hesp in the lungs of ALI mice. In addition, miR‐410 has been shown to target the inhibition of sex determining region Y‐box 18 (SOX18), indicating that Hesp might alleviate inflammatory secretion by blocking the miR‐410/SOX18 axis. Thus, Hesp might be a potential agent for the treatment of ALI.